Mononchid nematodes from Spain. Two species of Mylonchulus Cobb, 1916 inhabiting the coastal dunes of the Cádiz Gulf (Journal of Nematode Morphology and Systematics, 2012)
Mylonchulus rotundicaudatus(Skwarra, 1921) Schneider, 1939 was reported from Europe (Skwarra, 1921; Meyl, 1955; Mulvey, 1961; Kisiel, 1970, Loof, 1999) and North America (Mulvey, 1961). Recently, soil samples collected by Dr. P. Castillo yielded some specimens of this species from the coastal zone of Cadiz province, which constitutes a new record for the Iberian fauna. This contribution supplies additional information of this taxon, including morphometric data and microphotographs, which improve and complete our knowledge of the species. Moreover, the study of specimens collected in sand dunes from the adjacent Huelva coast reveals the occurrence of a new species, M. maritimus sp. n., which is illustrated and described here. Both species inhabiting similar habitats in Southwestern Spain.